Pengaruh Pola Asuh Orang Tua, Kedisiplinan Peserta Didik, dan Motivasi Belajar Terhadap Prestasi Belajar Peserta Didik: The Influence of Parenting Style, Student Discipline, and Learning Motivation on Student Learning Achievement - Rosyandi, Yudi; Afriza, Edi Fitriana; Hermawan, Yoni (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this study was to determine whether parenting style can affect student learning achievement, to determine whether discipline can affect student learning achievement, to determine whether learning motivation can affect student learning achievement, and to determine whether parenting style, discipline, and learning motivation collectively can affect student learning achievement. The method used by the author in this research is the survey method. The population in this study was all 180 students of class XI IPS (Social Sciences) at SMA Negeri 1 Ciamis, with the sampling technique used being proportionate random sampling, resulting in a sample of 125 students. The research findings show that there is a significant positive partial influence of parenting style, student discipline, and learning motivation on learning achievement. Furthermore, there is a significant simultaneous influence of parenting style, student discipline, and learning motivation on the learning achievement of students in the Economics subject for Class XI IPS at SMA Negeri 1 Ciamis.